Capacidade de inovação das cervejarias artesanais do Sul do Brasil - Ferras, Rosmeiri Aparecida Ribeiro (2018)
This study was developed from the point of view of innovation capacity, coming from the dynamic capacity. The research was based on the model of innovation capacity of Lawson and Samson (2001) who studies the capacity of innovation and seven factors related to it and that can influence the innovation of companies. The chosen field of study was the craft brewing market, seen that it stands by the news that has been showing through the creation of differentiated products such as beers and craft chopps with distinctive aroma and flavor. Thus, this study had as general objective to analyze the factors relationship of the model of innovation capacity of Lawson and Samson (2001) with the innovative capacity of craft breweries located in the South of Brazil. For this purpose, it was used the quantitative methodology. The research was conducted through the survey method using the likert scale 5 point. As a research instrument, it was used the instrument created by Valladares (2012) with some adaptations to the fact that brewer would be studied. Of 287 breweries that received the survey, 22 responses returned. The survey was sent to the breweries located in the States of Paraná, Rio Grande do Sul and Santa Catarina. SPSS software was used to perform the analyzes. Through the descriptive analysis it is possible to describe the profile of the breweries studied and prove that the innovation is present in the breweries by the creation of new craft products with different flavors and aromas. The statistical analysis showed a concordance of the companies in the factors that questioned the capacity of innovation and the application of the seven factors of the model studied. The Cronbach's Alpha analysis confirmed the reliability of the data. The analysis of non-parametric correlation of Kendal proved the relationship of factors of the model of innovation capacity studied allowing the analysis of the relationship between these factors with the innovation developed by breweries. The responses present several concordances in items that questioned the factors that potentiate the innovation. It is concluded that companies have a capacity for innovation because they seek to adapt to the environment through new experiments. For this, they insert the innovation in their strategic planning and invest in internal and external knowledge, organizational intelligence, in the creativity of the company, providing structure and culture favorable to innovation. They seek to develop their innovations with the use of technology, but in a smaller proportion than other factors. The applicability of this study was proven from the moment that the breweries studied requested access to the results in order to use the results to identify opportunities for improvement. The innovativeness of the dissertation comes as it studies a totally innovative market, seeking to understand their reality through a theoretical model.